ARK 2023: AWI airborne ultra-wideband radar data over the Müller Ice Cap, Umingmat Nunaat (Axel Heiberg Island), Canadian Arctic (The Müller Ice Cap Project) - Steinhage, Daniel; Jansen, Daniela; Franke, Steven; Helm, Veit; Lilien, David A; Dahl-Jensen, Dorthe (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the Alfred Wegener Institutes multi-channel ultra-wideband (AWI UWB) radar system during the Arctic season of 2023 in the Canadian Arctic. The profiles extend across the Müller Ice Cap on Umingmat Nunaat (Axel Heiberg Island), Nunavut, Canada, ∼80°N. The radar data show that some areas near the top of the ice cap are more than 600 m thick, have nearly stable surface elevation, and flow slowly, making them good candidates for an ice core with an undisturbed Holocene climate record (Lilien et al., 2024). The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: AWI UWB; Canadian Arctic; ice core reconnaissance; Müller Ice Cap; Polar 5; radio-echo sounding